2021
DOI: 10.3390/membranes11120992
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 and P-gp Mediated Herb-Drug Interactions and Molecular Docking Studies of Garcinol

Abstract: Garcinol is an active constituent of Garcinia indica and Garcinia cambogia. Recent studies have proven that garcinol has anti-inflammatory, anti-cancer, and anti-oxidant activities. The objective of this study was to evaluate the inhibitory effects of garcinol on the activities of the drug metabolizing cytochrome P450 (CYP) isozymes to predict potential herb-drug interactions with co-administered drugs. Garcinol was incubated with a mixture of rat liver microsomes and eight CYP probe substrate cocktail under o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…By comparing the differences in the docking forces between five biflavonoids and human CYP3A4, the results suggested that the formation of hydrogen bonds may be the molecular mechanism of inhibition. This was consistent with the previous studies, which reported that saikosaponin and garcinol with inhibitory effects of CYP3A4 also form hydrogen bonds with CYP3A4 (Bolla et al., 2021; Li et al., 2021). By analyzing the molecular structure of each compound, we found that amentoflavone, ginkgetin, and bilobetin have more hydroxyl groups in the structure, which were easy to form hydrogen bonds.…”
Section: Discussionsupporting
confidence: 93%
“…By comparing the differences in the docking forces between five biflavonoids and human CYP3A4, the results suggested that the formation of hydrogen bonds may be the molecular mechanism of inhibition. This was consistent with the previous studies, which reported that saikosaponin and garcinol with inhibitory effects of CYP3A4 also form hydrogen bonds with CYP3A4 (Bolla et al., 2021; Li et al., 2021). By analyzing the molecular structure of each compound, we found that amentoflavone, ginkgetin, and bilobetin have more hydroxyl groups in the structure, which were easy to form hydrogen bonds.…”
Section: Discussionsupporting
confidence: 93%
“…The authors observed that ADI can suppress activities of several CYP enzymes, including CYP2E1, and may be used in combination with other therapeutic regimens. Moreover, an active constituent of Garcinia indica and Garcinia cambogia, Garcinol, causes herb-drug interaction by inhibiting CYPs involved in drug metabolism [ 109 ]. In a previous study by Trousil et al, the authors included healthy controls and ovarian cancer patients, and gave them caffeine, chlorzoxazone, dextromethorphan, and omeprazole as in vivo probes to analyze CYP activity.…”
Section: Cyp2e1 In Clinical Drug-drug and Alcohol-drug Interactionsmentioning
confidence: 99%
“…2,3',4,4',5-Pentachlorobiphenyl (CB118) is specifically stabilized within CYP2B6 through hydrophobic contacts of V104 and L363 with the 5'-and 2-positions of CB118, respectively (Mise et al, 2016). Molecular docking studies of herbal medicines such as sauchinone and garcinol have revealed similar contributions of the hydrophobic CYP2B6 active site residues to substrate binding (Gong et al, 2018;Bolla et al, 2021). Nearly all residues interacting with triclosan and 2,2',4,4'-tetrabromodiphenyl ether (BDE-47) are nonpolar as well (Zhang et al, 2021).…”
Section: Functions and Plasticity Of Cyp2b6 Active Site Residuesmentioning
confidence: 99%